Development of Rectangular Microstrip Antenna Array for RFID-Based Automatic Locker Monitoring System Communication - Rahmawati, Yosy; Krisnawati, Luh; Raihan, Muhammad (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2025)
This study discusses the design and optimization of a rectangular array microstrip antenna operating at 2.4 GHz for use in an RFID-based locker monitoring system. The optimization process was carried out to enhance antenna performance based on key parameters such as return loss, VSWR, impedance, bandwidth, gain, and radiation pattern. Simulation and measurement results show significant improvement after optimization. The return loss improved from –46.5 dB to –27.6 dB, while the VSWR decreased from 4.964 to 1.000, indicating excellent impedance matching to a 50 Ω system. The bandwidth increased from 94.2 MHz to 126.3 MHz, exceeding the minimum requirement specified in ISO/IEC 18000-4 for 2.4 GHz RFID applications. The radiation pattern exhibits a main lobe at 2° with a maximum gain of 4.91 dBi and a side lobe level of –14.2 dB. These results demonstrate that the optimized antenna meets technical standards and is highly suitable for efficient implementation in fixed RFID reader systems.